Pengaruh Integritas, Etika Profesi, Kepatuhan Standar Audit terhadap Remote Audit dan Kualitas Audit Pada Auditor di Kantor Akuntan Publik Surabaya - Irma Retno Dewi; Tri Ratnawati (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
The purpose of this study is to investigate the influence of integrity, professional ethics, compliance with audit standards on remote audits and audit quality among auditors at the Surabaya Public Accounting Firm. The sample for this research was 63 auditors. Hypothesis testing in this research uses SmartPLS 3.0 with outer model and inner model tests. The results of this research indicate that Remote Audit does not have a significant effect on audit quality. So further studies are needed with an empirical approach to develop audit quality based on remote audits. Remote audits can occur due to remote audits carried out by auditors from separate locations. Remote audits utilize information and communication technology to collect data, analyze information, and conduct audits without the need to be physically present at the location being audited. Based on the research results, it can be concluded that not all Public Accounting Firms always pay attention to remote audits and the quality of those they audit.